The Role of Contemporary Information Technology in Developing Human Resource Management Strategies: A Field Study on the Egyptian Company for Trade and Distribution of Medicines - Eid, Samah (The Arab Journal of Administration, 2023)
This recent research deals with the means of information technology as the main pillar of human service and its field of work in order to secure, store, and deliver information after processing it and preparing it for the user quickly, accurately and comprehensively. The success of organizations in today’s world depends on what they have of human resources with high efficiency in terms of education, training, and experience, and what these organizations possess of modern and advanced technology that can be harnessed to serve their strategies and the vision, mission, goals and programs, and one of the most important ways to benefit from modern technology Finding interrelationships between them and the human resources available in the organization, and this administration requires the people in charge of the organization to define and accurately identify everything related to these interrelationships between information technology and human resources, and from these relationships, the issue of technology in Hussein and the development and activation of the functions of human resources management, through human resources management practices. Through this research deals with the impact of the use of information technology on human resource management strategies, which contributes to the improvement of the organization and the development and improvement of the performance of its human resources and thus impose itself in the labor market thanks to its dependence on modern technologies.